Subjugating Knowledges - Transmissional Traditions in School Education - Dorota Klus-Stańska (University of Lower Silesia, 2013)
In general, knowledge and tradition are credited with positive connotations. Popular definitions of knowledge carry surplus meaning evaluated even more positively than the attributes stereotypically assigned to tradition. In this article I intend to carry out preliminary recognition of the semiotics of what can be defined as a traditional model of a lesson, "reading into" the accepted definitions of knowledge, and teachers' and students' roles at school. In this way, I will try to identify the basic sources of such definitions. Later, I will reconstruct the selective effects of the inert maintenance of the concepts of knowledge and of the statuses and principles of the roles of teachers and students. Finally, I will indicate hypothetical reasons for why "the tradition of transmission" is maintained despite its disquieting results.